Bone mineral density in patients with chronic heart failure: a meta-analysis - Xing WM (Dove Medical Press, 2018)
Wenmin Xing,1,* Xiaoling Lv,1,* Wenyan Gao,2 Jirong Wang,1 Zhouxin Yang,1 Sanying Wang,1 Jing Zhang,1 Jing Yan1 1Zhejiang Provincial Key Laboratory of Geriatrics, Department of Geriatrics, Zhejiang Hospital, 2Institute of Materia Medica, Zhejiang Academy of Medical Sciences, Hangzhou, China *These authors contributed equally to this work Objective: This study aimed to verify the existing relationship between bone mineral density (BMD) and chronic heart failure (CHF) by meta-analysis. Methods: Databases, including PubMed, Web of Science, and Chinese National Knowledge Infrastructure, published in English or Chinese up to February 28, 2017, were searched for studies on the association between CHF and BMD. Two independent reviewers collected the relevant articles. The standard mean deviation (SMD) and 95% confidence interval were calculated for BMD with fixed- and random-effect models. Subgroup and sensitivity analyses were also conducted. Results: A total of six studies (552 CHF and 243 non-CHF patients) were included. The results indicated that the patients with CHF had a lower total BMD compared with the non-CHF patients. Similar effects were also observed for femoral neck, arm, leg, and trunk BMD. However, no difference was observed in the lumbar spine BMD. The SMD of total BMD in New York Heart Association classes I or II (NYHA I or II) patients was -0.62, while that in NYHA III or IV patients was -0.87, and the SMD of femoral bone mineral density in NYHA I or II patients was -0.47, while that in NYHA III or IV patients was -1.07. Moreover, vitamin D and parathyroid hormone (PTH) were also found to be associated with CHF. Conclusion: Patients with CHF had a lower total BMD and femoral neck, arm, leg, or trochanter BMD than patients with non-CHF. Vitamin D reduced, whereas PTH increased, with the severity of CHF. The clinical significance of the present findings remains uncertain and should be confirmed by future studies. Keywords: bone mineral density, chronic heart failure, meta-analysis